A Retrospective Study on the Imaging Spectrum of Functional Single Ventricle and Its Associations - B. Niva; Ramiah Rajeshkannan (Indian Journal of Radiology and Imaging)
Objective The aim of the study was to identify the various spectrum of single ventricle (SV) physiology and to correlate the anatomical variants.